MENGINTEGRASIKAN KONSEP RAHMATAN LIL ALAMIN DALAM KURIKULUM PENDIDIKAN ISLAM DENGAN PENDEKATAN HOLISTIK - Ismail; Tobroni; Faridi (LPPM STAI Muhammadiyah Probolinggo, 2024)
The concept of Rahmatan lil Alamin suggests that Islamic education can serve as a vehicle to improve human relations with nature, promote peace within society, and encourage sustainable spiritual and material development. This study aims to confirm the relevance of applying the concept of Rahmatan lil Alamin with a holistic approach at Madrasah Aliyah Muhammadiyah 01 Tegalombo. The research questions are formulated as follows: How does the integration of Rahmatan lil Alamin with holistic concepts manifest in the curriculum at Madrasah Muhammadiyah 01 Tegalombo? What are the implementation strategies for integrating Rahmatan lil Alamin with holistic concepts at Madrasah Muhammadiyah 01 Tegalombo? This qualitative research employs a case study approach. The findings reveal that Madrasah Aliyah Muhammadiyah 01 Tegalombo has successfully created an educational environment that is not only academic but also ethical and cultural. Their vision to produce academically and morally intelligent generations capable of being a mercy to all creation is reflected in their efforts to integrate Islamic values into the educational culture.